Impact of acute exacerbations of COPD on patients' health status beyond pulmonary function: a scoping review - Machado, A. (2022)
This scoping review summarized the evidence regarding the impact of acute exacerbations of COPD (AECOPD) on patients' health status beyond pulmonary function. PubMed, Embase, and Web of Science were searched. Prospective cohort studies assessing the health status of patients with COPD in a stable phase of the disease and after a follow-up period (where at least one AECOPD occurred) were included. An integrated assessment framework of health status (i.e., physiological functioning, complaints, functional impairment, quality of life) was used. Twenty-two studies were included. AECOPD acutely affected exercise tolerance, quadriceps muscle strength, physical activity levels, symptoms of dyspnoea and fatigue, and impact of the disease. Long-term effects on quadriceps muscle strength, symptoms of dyspnoea and depression, and quality of life were found. Repeated exacerbations negatively impacted the fat-free mass, levels of dyspnoea, impact of the disease and quality of life. Conflicting evidence was found regarding the impact of repeated exacerbations on exercise tolerance and physical activity levels. AECOPD have well-established acute and long-term adverse effects on health status beyond pulmonary function; nevertheless, the recovery trajectory and the impact of repeated exacerbations are still poorly studied. Further prospective research is recommended to draw firm conclusions on these aspects.